الهامش والمركز في رواية (الدوائر والأبواب) لعبد الوهاب عيساوي - إلهام سيساوي (My University, 2023)
Summary : This research contains a study of « the margin and the centre in the novel circles and doors by abdelwahab issaoui . The relationship between the margin and the center is an interactive and comlementary relationship since ancient times , but it has historically changed and deviated and thus sided with one party at the expense of the other and this was reflected in all aspects of human life , as this study came toreveal the extent of the penetration of this topic in the txt of the arab novel in general and the algerian in particular . The results of the study were considered proven , first, because the centre does not dominate the margins in all aspects , but there is a relationship of influence and vulnerability between each of them , secondly the novel circles and doors , has a goal by the writer , which is to restore considertion to the margina at the expense of centre . Thus, we find that this literary work contains this subject in most of its artistic characteristics , whith the aim of opening great prospects for suspense and creativity for the readers . ------------الملخص يحتوي هذا البحث على دراسة "الهامش والمركز في رواية الدوائر والأبواب لعبد الوهاب عيساوي " العلاقة بين الهامش والمركز علاقة تفاعلية تكاملية منذ القديم ، لكنها تاريخيا تغيرت وانحرفت وبالتالي انحازت إلى طرف على حساب الطرف الأخر ، وهذا ما انعكس على جميع الجوانب الحياتية للإنسان ، إذ جاءت هذه الدراسة للكشف عن مدى تغلغل هذا الموضوع في المتن الروائي العربي عامة و الجزائري خاصة اعتبرت نتائج الدراسة مثبتة أولا لعدم طغيان المركز على الهامش في جميع الجوانب ، بل هناك علاقة تأثير و تأثر بين كل منهما ن ثانيا أن توظيف هذا الموضوع في الأعمال الأدبية و خاصة رواية الدوائر و الأبواب له هدف من قبل الكاتب و هي إعادة الإعتبار للهامش على حساب المركز وبالتالي نجد إحتواء هذا العمل الأدبي على هذا الموضوع في معظم خصائصه الفنية ، وذلك لهدف فتح آفاق كبرى للتشويق و الإبداع بالنسبة للقراء ------------------- Résumé : Cette recherche contient une étude de ( la marge et le centre dans le roman cercles et portes d 'abdelwahab issaoui ) La relation entre la marge et le centre est une relation interactive et complémentaire depuis les temps anciens mais elle a changé et dévié donc elle s 'est rangée du coté d 'une partie au détriment de l 'autre et cela s 'est reflété dans tous les aspects de la vie humaine en particulier. Les résultats de l’étude ont été jugés avérés ,d’une part , parceque le centre ne domine pas le marges dans tous les aspects , mais il existe une relation d’influence et de vulnérabilité entre chacun d’eux , d’autre part , l’emploi de ce sujet dans les œuvres littéraires , en particulier les romans circles et portes , à un but par l’écrivain , qui est de reconsidérer la margeau détriment du centre . Ainsi, nous constatons que cette ouevre littéraire contient ce sujet dans la plupart de ses caractéristiques artistiques , dans le but d’ouvrir des grands perspectives de suspense et de créativité pour les lecteurs .